Does the Oxygen Content of Tolkien’s Middle Earth Allow for Greater Endurance? - Walker, Richard; Cooper-Dunn, Alice (Journal of Interdisciplinary Science Topics, 2017)
The Lord of The Rings is a quintessential fantasy trilogy in which human men perform many seemingly unachievable feats of heroism and athleticism. One such example would be Aragorn’s tireless defence of Helms Deep for an entire night. This paper investigates whether it is a feasible hypothesis to suggest that Middle Earth must have a higher oxygen content in order for the men of Rohan and Gondor to perform such physical tasks. Through using the gas exchange equation, estimating a 10% increase in atmospheric O2 concentration in Middle Earth when compared to Earth and using Aragorn as a test subject, this hypothesis could be true.